Difficulties in managing misbehavior of first grade english language learners = Những khó khăn trong việc quản lí hành vi không phù hợp của trẻ học tiếng Anh lớp một - Phan, Thị Thanh Hà (2020)
The purpose of this thesis is to identify teachers’ difficulties in dealing with misbehavior of first grade English language learners. To reach this aim, the researcher employed semi-structured interview and field observation to explore the common types of student misbehavior, underlying reasons behind them, troubles they cause, and teachers’ resolutions. Participants of this multiple case study are three Vietnamese teachers who teach English to first grade pupils at a primary school. Analysis of the collected data indicates that four major behavior problems of the pupils in question are chatting with friends, dealing with other things, talking out of turn and complaining about friends to the teacher. Factors determining such misbehavior types come from the children themselves and their surrounding environment. Not only drawing students’ attention out of the lesson, the behavior problems also distract the teaching process, thus indirectly affecting the learning flow of the entire class. To solve these problems, the teachers in question tend to encourage rather than punish the pupils. Their encouragement and punishment are usually applied to the whole group of students instead of the badly-behaved ones. Sometimes, to ensure the progress of the lesson, the teachers have no other choice but ignore the students’ misbehavior. Findings of the research might be a useful reference source for other researchers who intend to conduct studies on relevant topics. Moreover, inexperienced English teachers might also apply these findings in their classes for young learners. Last but not least, implications drawn at the end of this paper should be taken into consideration by the organizing board of this primary school.